2019
DOI: 10.1002/slct.201803128
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Products of Benzylamine Oxidation Catalyzed by Manganese Porphyrins: Some Factors that Play a Critical Role for Imine Formation

Abstract: This work describes the oxidation of benzylamine by PhIO, catalyzed by a series of first‐row metal salts and the respective first‐, second‐, and third‐generation metalloporphyrins. Five products were identified in reactions with [MnIIITPPCl]/PhIO. In this system, two products obtained (benzaldehyde oxime and N‐benzylbenzamide) were not previously described when [MnIIITPPCl] was used as catalyst. The change in the oxidant type (PhIO, PhI(OAc)2, H2O2 or m‐CPBA) modified the selectivity for the major product in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…7 Research from our lab and others has shown that Ru and Ir complexes of triazolylidene N-heterocyclic carbene (NHC) complexes to catalyze dehydrogenative amine homocoupling, when reacted at 150°C in toluene or 1,2-dichlorobenzene. [8][9][10] In an effort to lower costs and increase sustainability of the process, recent work has focussed on the use of non-noble metals such as Cu, [11][12][13][14] Mn, 15,16 and Fe, 17,18 with impressive results.…”
Section: Introductionmentioning
confidence: 99%
“…7 Research from our lab and others has shown that Ru and Ir complexes of triazolylidene N-heterocyclic carbene (NHC) complexes to catalyze dehydrogenative amine homocoupling, when reacted at 150°C in toluene or 1,2-dichlorobenzene. [8][9][10] In an effort to lower costs and increase sustainability of the process, recent work has focussed on the use of non-noble metals such as Cu, [11][12][13][14] Mn, 15,16 and Fe, 17,18 with impressive results.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic oxidation of 1 to its corresponding benzylidene imine has been proposed in previous studies as a benchmark reaction to assess the catalytic activity of graphenic materials (Figure ). Analogous works have also reported the presence of N -benzylbenzamide during benzylamine oxidation. , …”
Section: Resultsmentioning
confidence: 69%
“…36 Analogous works have also reported the presence of Nbenzylbenzamide during benzylamine oxidation. 37,38 Table 2 summarizes the results of aerobic oxidation of 1 under solvent-free conditions at 80 °C using the series of rGO materials as catalysts. It should be noted that this reaction has been frequently reported using noble 39 or transition metalbased catalysts at reaction temperatures higher than 120 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Such substrates have previously been photooxidized to N-benzylidenebenzylamines using of photoexcited oxygen as a sustainable and harmless source of oxidant (Scheme 1,II). A wide range of photocatalysts has indeed been utilized: organometallic complexes, [51 -53] Fe(II) grafted on carbon nitride, [54] porphyrin-type photocatalysts, [55][56][57][58] organic dyes, [59,60] porous polymers, [49,[61][62][63] metal-organic framework, [64,65] graphene quantum dot materials, [66,67] TiO 2 , [68 -71] or other semi-conductors. [72 -75] We thus envisioned developing a photooxidative approach for the direct synthesis of complex α-aminophosphorus compounds using benzylamine derivatives and phosphinylidenes as simple and readily available starting materials (Scheme 1,III).…”
Section: Introductionmentioning
confidence: 99%